IMPROVING THE WELL-BEING OF BUSINESS PARTICIPANTS THROUGH THE HALAL CERTIFICATION ASSISTANCE BY BAKORWIL IV PAMEKASAN FROM THE PERSPECTIVE OF MAQASID SHARIA: PENINGKATAN KESEJAHTERAAN PELAKU USAHA MELALUI PENDAMPINGAN SERTIFIKASI HALAL BAKORWIL IV PAMEKASAN DALAM PERSPEKTIF MAQASID SYARIAH - Mohammad Hasan, Hasan; Farid Ardyansyah, Khoirun Nasik (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
One of the indicators of achieving increased prosperity for business operators can be observed through the widening market share of the products they produce. To expand market share, a product must comply with its legal aspects and increase consumer interest, including obtaining halal certification. This research aims to assess the enhancement of halal certification while considering the principles of Maqasid Sharia. This is a qualitative field research study conducted by gathering data and information through interviews, observations, and documentation. The research results indicate that halal certification contributes to building consumer trust and increasing revenue obtained from the expanding market share. Halal standardization refers to the halal assurance system of MUI. From the perspective of Maqasid Sharia, halal certification is oriented toward preserving religious, spiritual, intellectual, lineage, and wealth aspects